Scholarinine A, a N3 type caged-monoterpene indole alkaloid as Cav3.1 T-type calcium channel inhibitor from Alstonia scholaris. Issue 1 (2nd January 2020) - Zhan, Rui; Du, Shu-Zong; Duan, Zhi-Hang; Nian, Yin; Chen, Ye-Gao
Graphical abstract: Highlights: Scholarinine A (1 ) is a new N 3 -type caged MIA with 6/5/6/5/5/6 fused ring system from Alstonia scholaris . X-ray diffraction analysis confirmed the absolute configuration of 1 . Bioassay proved that 1 was both Cav 3.1 TTCC inhibitor and neurite outgrowth promoter. Abstract: Scholarinine A (1 ), a new N3 -type caged monoterpene indole alkaloid was isolated from the branches and leaves of Alstonia scholaris . Structurally, 1 is featured by unique 6/5/6/5/5/6 carbocyclic skeleton bearing a novel imidazolidine ring E. The structure of 1 was determined by extensive spectroscopic analyses and X-ray crystallography. Biological studies exhibited that compound 1 is a potent Cav 3.1 T-type calcium channel inhibitor with an IC50 value of 4.28 μM. In addition, 1 enhanced the neurite outgrowth of nerve growth factor (NGF) mediated PC12 cells at 10 μM.